The effect of paternal anxiety on mother-infant bonding in neonatal intensive care - Mark Ettenberger; Łucja Bieleninik; Andreas Størksen Stordal; Claire Ghetti (BMC, 2024)
Abstract Background The hospitalization of a preterm infant in the NICU can lead to mental health difficulties in parents, but not much is known how paternal anxiety might affect the mother-infant relationship. Methods This prospective cohort study is a secondary analysis investigating how paternal anxiety levels might affect maternal bonding in the NICU using the dataset of the multinational pragmatic randomized controlled trial LongSTEP. A linear mixed-effects model was used for correlations of paternal anxiety (GAD-7) and maternal bonding (PBQ) at NICU discharge, and at 6 and 12 months infant corrected age. Secondary analyses examined effects on paternal anxiety related to: site (Argentina, Colombia, Israel, Norway, and Poland), maternal depression (EPDS), infant gestational age at birth, paternal age, and type of pregnancy. Results Paternal anxiety did not predict maternal bonding at NICU discharge (p = 0.096), at 6 months (p = 0.316), or at 12 months infant corrected age (p = 0.473). Secondary outcomes showed a statistically significant site effect, with higher paternal anxiety levels at the two Colombian sites at baseline (p = 0.014 and p = 0.020) and for one site at discharge (p = 0.012), but not for paternal age (p = 0.925 and p = 0.793), infant gestational age at birth (p = 0.974 and p = 0.686 and p = 0.340), or type of pregnancy (p = 0.381). Maternal depression predicted paternal anxiety at baseline (p < 0.001) and at discharge (p = 0.003). Conclusions In this study, paternal anxiety did not predict maternal bonding. Paternal anxiety varied by site, indicating a need for research on potential cultural differences in manifestation of paternal anxiety. Maternal depression predicted paternal anxiety, confirming a previously reported correlation. Further research on variations in paternal mental health in the neonatal period is warranted, as well as exploration of the social contagion of mental health in preterm parents. Trial registration ClinicalTrials.gov NCT03564184.